Using Music to Develop a Multisensory Communicative Environment for People with Late-Stage Dementia. (8th December 2019) - Clare, Amy; Camic, Paul M; Crutch, Sebastian J; West, Julian; Harding, Emma; Brotherhood, Emilie
Abstract: Background and Objectives: Research has indicated the benefit of music interventions on biological, psychological, and cognitive aspects of dementias, yet there is limited research focusing on music's role in communication. This study developed a conceptual understanding of how people with late-stage dementia may express themselves nonverbally and interact with others during a live music group over time. Research Design and Methods: Eight people with advanced dementias in residential care (aged 82–97 years), four care staff, and three musicians participated in 8-hr-long weekly live Music for Life sessions and listened to 1-hr-long recorded music session. Visual grounded theory was used to analyze video data collected nonintrusively via the Fly 360-degree camera. Results: The live music group facilitated a multisensory communicative environment allowing for verbal and nonverbal communicative actions, social interactional components and agency to develop over time. These aspects were influenced by three factors: time, one-to-one interaction within a group setting and the characteristics of the music. Discussion and Implications: Nonverbal communication in later-stage dementia may be overlooked or underestimated by busy care staff and families. Using music as an interactive way to communicate can help develop mirroring and turn-taking which has been shown to improve quality of life for people with communication impairment, increase their nonverbal communication and allow for a connection to be built between people. Although further research is recommended, individuals responsible for residential care should feel confident that the development of ongoing music groups for this population is warranted as part of ongoing care.